Role of autotaxin in systemic lupus erythematosus - Tsuchida, Yumi; Shoda, Hirofumi; Sawada, Tetsuji; Fujio, Keishi (Frontiers in Medicine, 2023)
Systemic lupus erythematosus (SLE) is a prototypic systemic autoimmune disease characterized by the production of various autoantibodies and deposition of immune complexes. SLE is a heterogenous disease, and the pattern of organ involvement and response to treatment differs significantly among patients. Novel biological markers are necessary to assess the extent of organ involvement and predict treatment response in SLE. Lysophosphatidic acid is a lysophospholipid involved in various biological processes, and autotaxin (ATX), which catalyzes the production of lysophosphatidic acid in the extracellular space, has gained attention in various diseases as a potential biomarker. The concentration of ATX is increased in the serum and urine of patients with SLE and lupus nephritis. Recent evidence suggests that ATX produced by plasmacytoid dendritic cells may play an important role in the immune system and pathogenesis of SLE. Furthermore, the production of ATX is associated with type I interferons, a key cytokine in SLE pathogenesis, and ATX may be a potential biomarker and key molecule in SLE.